Linking information and energy—activity-based energy-aware information processing. (April 2013) - Hu, Xiaolin; Zeigler, Bernard P
We present an activity-based framework that links information and energy. The activity-based framework uses a quantization-based approach for modeling information processing and defines weighted activity to model the energy consumption of information processing. We provide a formal description of this framework and use simulation to show how it enables one to study the interaction between information and energy in energy-aware information processing. An existing discrete event system specification (DEVS)-based simulation environment, DEVS-FIRE, is employed to model wireless sensor nodes for detecting and monitoring wildfires. Simulation experimental results confirm the utility of the activity-based framework to support the analysis and design of energy-aware information processing systems.